2017
DOI: 10.11591/edulearn.v11i1.4669
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Resilience in Remote Islands Area: A Case Study in Small Pagerungan Island Sumenep Regency, Indonesia

Abstract: This study aims to describe resilience teacher at Elementary school III at Small Pagerungan Island. Aspects of resilience in this study are phase of resilience refers to Patterson & Kelleher (2005) and the strategy of resilience refers to Diah & Pradna (2012). This type of research is descriptive qualitative with case study approach. The subjects were 5 teachers (Subject I: government employee (PNS) teachers senior and immigrant from Java, Subject II: government employee (PNS) teachers senior natives, subject … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 19 publications
1
7
0
3
Order By: Relevance
“…The teacher must be brave enough to take the new step in the learning process that is carried out. It is in line with the research conducted by Osman et al in Nurwidodo et al (2017) stating that a teacher should have the power to experience any challenges in the educational field.…”
Section: Introductionsupporting
confidence: 88%
“…The teacher must be brave enough to take the new step in the learning process that is carried out. It is in line with the research conducted by Osman et al in Nurwidodo et al (2017) stating that a teacher should have the power to experience any challenges in the educational field.…”
Section: Introductionsupporting
confidence: 88%
“…Someone is resilient if he is surrounded by stressful circumstance in which they do not have control over it (Rizqi, 2017). Teachers need to be resilient as Nurwidodo, et al (2017) affirm that "the ability to survive in difficult conditions is a remarkable thing" (p. 49).…”
Section: Resiliencementioning
confidence: 99%
“…For instance inadequate teaching resources, facilities or government support. Those factors happen in rural areas of Indonesia (Nurwidodo, Husamah, Rahardjanto, Mas'odi, & Mufrihah, 2017;Lomi & Mbato, 2020;Florida & Mbato, 2020). Study conducted by Nurwidodo, et al (2017) reveals that teachers in rural area are resilience to cope with insufficient situation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, teachers of physical education in a special school have to show creativity, ability to work in varying conditions, acceptance of professional defeats, when despite educational efforts the intended effects often are not achieved within the expected time and scope. The study by Nurwidowo et al [33] showed that better functioning and also the ability to adapt to the demanding working conditions in teachers can ensure an appropriately high level of resiliency. Also Ellison [34] claims that a high level of resiliency is responsible for professional success in physical education teachers from special schools and is also of the view that resiliency is not a permanent trait and its level may be increased by introducing specially developed training programs.…”
Section: Wwwbalticsportsciencecom Dicscussionmentioning
confidence: 99%